A research on groupware on personal digital asisstance (PDA) for student's activities / Fauziah Mustafa - Fauziah, Mustafa (2004)
This thesis focuses on the research of the groupware application on the PDA based on student's environment. The objective of this research is to study and analyze the suitable groupware application for students, to research the capability of groupware application on the PDA in terms of hardware, software and the network and also to develop the appropriate user interface based on the groupware application. Questionnaires were distributed to the students of Mara University of Technology. On the whole, it can be said that 72% of the respondents and about 81% of the respondents know what is PDA and the terms of groupware. Finally from this research the user interfaces based on the groupware application was created in order to support student's environment using Personal Digital Assistance. Hopefully, it will help to increase the use of PDA among the students, and also help student to connect each other by using this kind of groupware applications.